Fully selective catalytic oxidation of NO to NO2 over most active Ga-PCH catalyst. Issue 2 (April 2020) - Kashif, Muhammad; Yuan, Minhao; Abduallah, Montaser; Su, Yaxin
Highlights: Catalytic oxidation of NO over x Ga-PCH catalysts were conducted. The 24 wt % Ga-PCH showed 100 % catalytic oxidation of NO at 150 °C. The Ga2 O3 promoted highly amorphous formation and Lewis acidic sites. High Lewis acidic site, which increased the NO oxidation at low temperature. Abstract: The series of xGa-PCH catalysts were prepared by the impregnation method for low temperature selective catalytic oxidation of NO in the excess of O2 and characterized by N2 adsorption-desorption, XRD, SEM, Py-FTIR, XPS, O2 -TPD, and NO-TPD. The experimental study and characterization results were demonstrated that among all the samples, the 24Ga-PCH catalyst was highly active and had superior catalytic properties and never has been reported yet. The 24Ga-PCH catalyst exhibited high catalytic efficiency and 100 % NO oxidation at low temperature (150 °C). The effect of gallium loading, the effect of carriers, influence of O2, temperature and catalytic oxidation of NO with function time-on-stream were studied in detail. Meanwhile, the NO conversion experiment, SEM and Py-FTIR tests indicated that a small amount of gallium oxide on PCH result on considerable improvement in the catalytic performance, because of the higher acidic site and amorphous formation which were beneficial for NO oxidation at low temperature.